1994
DOI: 10.1177/0011128794040003004
|View full text |Cite
|
Sign up to set email alerts
|

Officers' Response to Community Policing: Variations on a Theme

Abstract: Few evaluations of community policing consider the program's effect on officers' attitudes about community policing or job satisfaction. The mixed results we do have are difficult to synthesize for numerous reasons, including the substantial variation in program design and implementation. This article examines variations in officers' attitudes across three different community policing programs in one department, using 11 scales for community police attitudes and 5 scales for job satisfaction. The programs vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 2 publications
1
43
3
Order By: Relevance
“…Strategy-related behavior was assessed using a seven-item scale measuring the frequency of communitypolicing activities identified in the law enforcement literature, such as attending youth programs, working to solve problems in the comreunify, and making presentations to community groups (Brown & Wycoff, 1987;Greene, 1987;Rosenbaum et al, 1994;Wilson & Bennett, 1994). The participants responded using a 5-point Likert scale with anchors ranging from frequently to never (a = .87).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategy-related behavior was assessed using a seven-item scale measuring the frequency of communitypolicing activities identified in the law enforcement literature, such as attending youth programs, working to solve problems in the comreunify, and making presentations to community groups (Brown & Wycoff, 1987;Greene, 1987;Rosenbaum et al, 1994;Wilson & Bennett, 1994). The participants responded using a 5-point Likert scale with anchors ranging from frequently to never (a = .87).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have also examined the impact of departmental-level factors on officers' job satisfaction and on-the-job behavior, such as the level of participatory management practices (Wycoff & Skogan, 1994), the amount of training provided (Rosenbaum et at., 1994), and the relationship between officers and their supervisors (Wilson & Bennett, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that when officers feel competent in community policing efforts, and acknowledged for these efforts by the community, they have the highest job satisfaction (Wilson & Bennett, 1994). Increased officer morale and feeling part of an important program and approach to a public health problem like domestic violence are significant outcomes in and of themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are subtle differences among police organizations in understanding community policing, the common denominator for all community policing is strengthening harmony between police and its community. Wilson and Bennett (1994) suggested that, to strengthen the harmony between police and its community, police departments should consider the contextual factors surrounding officers' attitudes toward communities and that departmental programs for community policing must be designed with communities rather than solely designing at the departmental level.…”
Section: )mentioning
confidence: 99%